STUDY OF A WASTE HEAT RECOVERY ORGANIC RANKINE CYCLE FROM A SULFIRIC ACID PRODUCTION PLANT - Ali, Nawel Ben; mabrouk, Aycha; Hajji, Nejib (IJRDO-Journal of Applied Science, 2021)
In this paper, the study of electrical energy production by Organic Rankine Cycle (ORC’s) was considered for the valorization of waste eat stemming from a sulfuric acid production plant. First, a sensitivity analysis was carried out to study the effect of different operating parameters on the thermal efficiency of the cycle. These parameters include the evaporation pressure, the evaporation temperature, the condensation temperature, the cooling water temperature as well as the efficiency of the turbine and the pump. Energy calculations were obtained from the process simulation with Aspen HYSYS. A total of 24 potential working fluids were considered in this study with emphasis on ammonia. The selection among them was based not only on thermal efficiency but also on environmental and safety considerations. Benzene and ammonia were found to be the most efficient. Results proved that it is possible to produce 7 MW of electricity in the considered plant using ORC’s.